Violencia física y su incidencia con las relaciones interpersonales de una joven de 28 años de la ciudad de Babahoyo - Vallejo Delgado, Aranxa Lisbeth (2023)
The following case study "Physical violence and its incidence with the interpersonal relationships of a 28-year-old girl from the city of Babahoyo", was based on the fact that physical violence is currently occurring a lot worldwide, affecting the mental health of people and inferring negatively on interpersonal ties. To collect the pertinent information from the patient, it was done through clinical observation, clinical history, and psychometric batteries, such as the Traumatic Experiences Questionnaire (TQ) and Post-Traumatic Stress Test, which allowed support for the presumptive diagnosis. Findings that served to trigger the pathology were detected, which were that since she got married she received verbal abuse from her husband because he was very jealous, likewise, he gave her strong blows, causing her to remain unconscious for 2 days, from as a result, he was left with a severe injury to his leg, making it difficult for him to walk and presenting problems with his mental health. According to everything used, it was possible to reach the patient's condition with the help of diagnostic manuals such as DSM-V and CIE-10, resulting in F43.10 (3009.81) Post-traumatic stress disorder, for which Cognitive Therapy was implemented. -Aron Beck's Behavioral to reduce symptoms, the techniques provided were differentiating facts, thoughts and feelings, explaining how thoughts generate feelings, examining evidence, generating an alternative explanation, training in social skills and 4-step breathing.